Quasar Properties from the Sloan Digital Sky Survey. III. The Quasars Obtained by the SDSS-IV - Wei-Rong Huang; Zhe-Geng Chen; Zhi-Fu Chen; Xiao-Feng Li (The Astrophysical Journal Supplement Series, 2023)
This paper provides the compilations of properties of the quasars newly obtained by the Sloan Digital Sky Survey (SDSS) during the fourth stage (SDSS-IV). The catalog is available on the journal's website. We have measured the main properties of emission lines around C iv , Mg ii , H β , and H α spectral regions. We estimate the quasar redshifts from our fits of narrow [O iii ], broad Mg ii , and broad C iv emission lines and find that the best redshifts included in DR16Q are robust with respect to our measurements. Based on the broad C iv , Mg ii , H β , and/or H α emission lines, we calculate the virial black hole mass with empirical relationships provided by previous works. Systematic biases are found among the different line-based mass estimators.